Real-time control of a permanent magnet synchronous motor drive (I) - Ko, Angus Yee Chow (2014)
This report documents the design work progress stages that have been carried out in the Final Year Project (FYP) which involved in the analysing and operating a real-time control of a Permanent Magnet Synchronous Motor (PMSM) that uses Digital Signal Processor (DSP) and will be conducted in the form of a closed-loop feedback system that relies on the Field Oriented Control (F.O.C.) or Vector Control technique. The report firstly reviews the research works done this area of expertise and literature review on using the TMS320F28335 DSP for synchronous motor such as PMSM which is capable to fulfil enhanced and efficient operation that improve performances. Next, it narrows down into the main fundamental background concepts that involve both on the hardware and software implementations that are required to use the F.O.C. technique on the project which simulation and actual physical experimental practices were being carried out to evaluate the performance, in terms of response, efficiency and accuracy. Furthermore, several issues mainly on the hardware implementation section were also being identified and discussed as well. The report finally provides suggestions for improvements to the F.O.C. approach and also offers recommendations for future work operation. An Appendix has been attached to this report. It comprises of the specifications and schematic circuit diagrams of various hardware circuit components were being design as well as the DSP interface features that were being selected to be implemented in the project.